2004
DOI: 10.1021/ja047816a
|View full text |Cite
|
Sign up to set email alerts
|

Invertible Amphiphilic Homopolymers

Abstract: Stimuli-responsive polymers and assemblies are viable candidates for the so-called "smart" materials. In this communication, we report a new class of amphiphilic homopolymers that forms micelle-like structures in polar solvents and inverted micelle-like structures in apolar solvents. We demonstrate that these superstructures are the result of the changes in the molecular-level conformations in the monomer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
130
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(133 citation statements)
references
References 15 publications
1
130
2
Order By: Relevance
“…3 We have recently developed a molecular design based on homopolymers in which both the hydrophilic and the hydrophobic moieties are incorporated within the monomer unit. 4 In that preliminary communication, we had demonstrated that such homopolymers are capable of providing both micelle-like and inverse micelle-like assemblies depending on the solvent environment, which is an amplified consequence of the molecular level conformational changes in each monomer unit. Since then, we have shown that such polymer assemblies are indeed unique and therefore could find complementary applications in a broad range of areas.…”
Section: Introductionmentioning
confidence: 97%
“…3 We have recently developed a molecular design based on homopolymers in which both the hydrophilic and the hydrophobic moieties are incorporated within the monomer unit. 4 In that preliminary communication, we had demonstrated that such homopolymers are capable of providing both micelle-like and inverse micelle-like assemblies depending on the solvent environment, which is an amplified consequence of the molecular level conformational changes in each monomer unit. Since then, we have shown that such polymer assemblies are indeed unique and therefore could find complementary applications in a broad range of areas.…”
Section: Introductionmentioning
confidence: 97%
“…A molecular basket was obtained by linking four cholate units to a cone-shaped calix [4]arene scaffold through azobenzene spacers. The molecule turns its polar faces inward in nonpolar solvents to bind polar molecules such as sugar derivatives.…”
mentioning
confidence: 99%
“…Azobenzene-derived calixarenes have attracted considerable interest of supramolecular chemists 9 ever since Shinkai and coworkers discovered the autoaccelerative diazo coupling of calix- [4]arene. Many calixarenes with azobenzene at the upper rim have been prepared according to Shinkai's method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…That low stability can be attributed to hydrogen bonding interactions between alcohol molecules and residual hydrophilic silanol moieties in the material. The literature reports evidence similar phenomena, leading to the formation of spherical structures with a random-coil backbone conformation, for oligomers with large aromatic [58,59], dendritic [60] or amphiphilic [61,62] side groups. Analogously, rigid rodflexible coil block copolymers can self-assemble in selective solvents into specific nanostructures with morphology governed by the geometric disparity between the rod and coil segments and anisotropic interactions between rod blocks (formation of liquid crystalline or crystalline structures) [63,64].…”
Section: Dynamic Light Scattering Studies Of Ph-lpsq Micellesmentioning
confidence: 68%